Utilization Of Audio Visual Media In Interactive Learning At SDN 1 Teniga In The 2024/2025 Academic Year - Sukardi Sukardi; Raden Sumiadi; Muhammad Muhajirin (Jurnal Ilmiah Mandala Education (JIME), 2025)
The purpose of this research is to describe the form of audio visual media and its use in managing interactive learning at SDN 1 Teniga in the 2024/2025 school year and to describe the process of using audio visual media in interactive learning at SDN 1 Teniga in the 2024/2025 school year. The research method used is descriptive qualitative research with the Milles and Hubberman research design model.The results of the study 1) show that the forms of audio visual media used in managing interactive learning at SDN 1 Teniga are in the form of audio visual media based on animated learning videos and game-based learning media (gamefication) such as quiz. The learning media is used during the learning process in the classroom. 2) The use of audio-visual media in interactive learning at SDN 1 Teniga begins with initial planning, determining learning objectives, selecting and creating animated videos and quizzes. Followed by implementation in the classroom starting from the opening greeting, reminding the previous material, showing animated video-based material, then the teacher invites students to discuss the learning material and finally the evaluation using the quiz application.